The expression in soil bacteria of symbiotic genes from Rhizobium leguminosarum biovar trifolii : a thesis presented in partial fulfilment of the requirements for the degree of Master of Science in Microbiology at Massey University - Fenton, Michael (Massey University, 1994)
Rhizobium leguminosarum biovar trifolii strain ICMP2163::Tn5 was able to spontaneously transfer its pSym to the non-nodulating Rhizobium loti soil isolate NR40 in sterile soil microcosms containing Ramiha hill soil or Ashurst silt loam soil at pH 6.0 or higher. In sterile soil microcosms at pH 6.0 containing sterile ryegrass or white clover plants the frequency of NR40 transconjugants was higher than in microcosms containing soil alone. The survival of the parent strains decreased in soil with a pH of 5.5 or less, and no transconjugant NR40 bacteria were detectable. Southern blots of the genomic digests probed with nodA DNA confirmed that transconjugant NR40 contained symbiotic genes. On artificial media strain ICMP2163::Tn5 transferred its symbiotic plasmid, by conjugation, to Sphingobacterium multivorum, an organism that can be found in soil. The transconjugant bacteria were able to nodulate white clover seedlings but were unable to fix nitrogen. Microscopic examination revealed that the root nodule structure, and bacteroid formation, were abnormal. The bacteria occupying the nodules were isolated and the total DNA extracted. The partial 16S RNA gene sequence from a transconjugant derived from a nodule was shown to be identical with that of the recipient S. multivorum. Southern blots of the genomic digests probed with nodA DNA confirmed that the transconjugant contained symbiotic genes. A Caulobacter crescentus sewage isolate was also able to induce a tumour like growth on white clover seedlings after receiving the pPN1 co-integrate plasmid from E.coli strain PN200. Eckhardt gel analysis confirmed that the transconjugant Caulobacter carried the R68.45:pSym co-integrate plasmid. Bacteroids were absent but Caulobacter cells were found in the outer two or three layers of the growth and the plant cells in this region had degenerated. Sequence data was obtained for a 260 bp fragment of the 16S rRNA gene from Sphingobacterium multivorum and Caulobacter crescentus corresponding to postions 44 to 360 on the Escherichia coli genome. A distance matrix was constructed showing the relationship between S. multivorum, C. crescentus, Rhizobium, and related bacteria and neighbor-joining was used to construct a tree. From the tree given it is concluded that the ability to carry or express symbiotic genes is not dependant on having a phylogenetic relationship with Rhizobium.
Keywords: Root-tubercles; White clover; Roots